Acupuncture as an Adjunctive Treatment for Post-stroke Epilepsy: Protocol for a Randomized Controlled Trial - Zhang, Yang; Zhao, Meidan; Zhang, Baozhen; Zhang, Kai; Zhou, Zhen (Frontiers in Neurology, 2021)
Background: Acupuncture has been clinically used to treat epilepsy after stroke. However, most of the current clinical studies are observational studies, and there are few well-designed randomized controlled trials (RCTs). Hence, we designed a multicentre RCT to assess the advantages and efficacy of acupuncture for post-stroke epilepsy (PSE). Methods/design: This is a two-arm, parallel, participants-blinded and assessor-blinded and multicentre RCT. A total of 120 patients with PSE aged from 18 to 75 years will be randomly assigned to two groups (routine treatment plus acupuncture group and routine treatment plus sham acupuncture group) at a 1:1 ratio. The participants will perform acupuncture or sham acupuncture treatment three times a week and be ongoing 8-week treatment. The primary endpoint is the proportion of seizure-free patients. A safety profile will be established. We will record adverse events for the safety evaluation. Discussion: The study will provide high-quality clinical evidence on the effectiveness and safety of acupuncture for treating patients with epilepsy after stroke. Trial registration: Chinese Clinical Trial Registry ChiCTR2100046114.